Análise e avaliação dos modelos de padronização de dados e procedimentos eletrônicos para desenhos e projetos da construção civil: estudo de caso - Frosch, Renato (Universidade Federal de São Carlos, 2004)
This present work intends to analyze and evaluate a set of proposals, in discussion, about the utilization feasibility of preceding pattern models (AsBEA proposal, AIA-CSI, ISO), related to the CADD technology development used in civil construction projects, emphasizing a graphical representation and the information transference. From the previous proposal, there were checked alterations caused on the elaboration routine of projects through a questionnaire application to active professionals on the elaboration, edition and review of electronic drawings and case study. (builder and projects office). Aiming verify the adaptation of a set of old rules (NBRs related to traditional technical drawing) to a new concept based on a system of standard computerized technical drawing, finally, this work intends to put up subsidies for a national technical rule/manual elaboration. Expecting that the development of this work can contribute to the deepen of projects related studies, specifically, on the organization feasibility aspects and nomenclature definition, and the graphical representation appreciation suited to electronic drawings.
Keywords: Desenho técnico; CAD; Normalização; Normas técnicas; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL